Performance evaluation of therapeutic feeding centers through efficiency, effectiveness and utilization of bed capacity: A retrospective quantitative study - Ahmed Alhidary; Pesigan Arturo; Ali Al-Waleedi; Ferima Coulibaly-Zerbo; Omar Faisal; Mahammad Al Mansour; Ali AL-Mudwahi; Mohammed Rajamanar; Ezechiel Bisalinkumi; Eshrak Al-Falahi; Latifah Ali (PLoS ONE, 2025)
The balance between wise use resources and provision of health services are crucial for the sustainability of services and ensuring value for money. Thus, it is essential to regularly monitor the status of health services to address any variations that arise. This study aimed to evaluate the performance of Therapeutic Feeding Centers (TFCs) by examining their efficiency, effectiveness, and beds utilization and assessing related factors. A retrospective quantitative study was conducted in 94 TFCs in Yemen from January to December 2022. Clinical outcomes like recovery rates, death rate, and default rate were measured, alongside with the dependent variables of efficiency, bed utilization, and effectiveness as a matrix to evaluate the TFC performance. The Data Envelopment Analysis model was used to measure technical efficiency, the Pabon Lasso model was used to classify the performance levels. The regression coefficient was used to determine associated factors. A total of 26,887 records of Sever-Acuate-Malnutrition children were reviewed. The results indicated that the recovered rate 90%, default rate 3.6%, death rate 1. 3%. The average effectiveness scores were 95%, technical efficiency 73%, and bed utilization rate 63%, the average performance was 82%. Moreover, the study found a positive weak correlation between effectiveness and efficiency (r = .190, n = 94, p = .008), and the efficiency was influenced by the Occupancy Bed Rate, Bed Turnover Rate and Length of Stay, F (3,90) =123.90, P < 0.001, R2 = .805. The results indicate that the TFCs performed well overall and even exceeding Sphere standards thresholds for the outcome and effectiveness indicators. However, there is still a need to improve efficiency and bed utilization to meet the standards. The study indicated to a positive correlation between effectiveness and efficiency, although no relationship has been found between them. To further performance enhancement, the ministry of health and its partners must optimize resources utilization.